Risk factors for poor multidrug-resistant tuberculosis treatment outcomes in Kyiv Oblast, Ukraine. Issue 1 (December 2017) - Aibana, Omowunmi; Bachmaha, Mariya; Krasiuk, Viatcheslav; Rybak, Natasha; Flanigan, Timothy; Petrenko, Vasyl; Murray, Megan
Abstract Background Ukraine is among ten countries with the highest burden of multidrug- resistant TB (MDR-TB) worldwide. Treatment success rates for MDR-TB in Ukraine remain below global success rates as reported by the World Health Organization. Few studies have evaluated predictors of poor MDR-TB outcomes in Ukraine. Methods We conducted a retrospective analysis of patients initiated on MDR-TB treatment in the Kyiv Oblast of Ukraine between January 01, 2012 and March 31st, 2015. We defined good treatment outcomes as cure or completion and categorized poor outcomes among those who died, failed treatment or defaulted. We used logistic regression analyses to identify baseline patient characteristics associated with poor MDR-TB treatment outcomes. Results Among 360 patients, 65 (18.1%) achieved treatment cure or completion while 131 (36.4%) died, 115 (31.9%) defaulted, and 37 (10.3%) failed treatment. In the multivariate analysis, the strongest baseline predictors of poor outcomes were HIV infection without anti-retroviral therapy (ART) initiation (aOR 10.07; 95% CI 1.20–84.45;p  0.03) and presence of extensively-drug resistant TB (aOR 9.19; 95% CI 1.17–72.06;p  0.03). HIV-positive patients initiated on ART were not at increased risk of poor outcomes (aOR 1.43; 95% CI 0.58–3.54;p  0.44). There was no statistically significant difference in risk of poor outcomes among patients who received baseline molecular testing with Gene Xpert compared to those who were not tested (aOR 1.31; 95% CI 0.63–2.73). Conclusions Rigorous compliance with national guidelines recommending prompt initiation of ART among HIV/TB co-infected patients and use of drug susceptibility testing results to construct treatment regimens can have a major impact on improving MDR-TB treatment outcomes in Ukraine.